RECENT UPDATE OF ZERUMBONE AS ANTI-COLON CANCER AGENT: A REVIEW - Sarmoko Sarmoko; Riri Fauziyya; Miralda Zahra; Nisa Yulianti Suprahman; Winni Nur Auli; Arif Ashari (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Colorectal cancer (CRC) remains a leading cause of cancer-related deaths worldwide, with limited effective therapies due to drug resistance and adverse effects. Zerumbone, a sesquiterpene isolated from Zingiber zerumbet Smith, has emerged as a promising natural anticancer agent. This review examines zerumbone's anti-colorectal cancer properties, including induction of apoptosis and cell cycle arrest, inhibition of invasion and metastasis, anti-angiogenic activity, and anti-inflammatory effects. Additionally, zerumbone demonstrates antioxidant properties, modulates gut microbiota composition, and targets multiple signaling pathways involved in CRC pathogenesis. Structure-activity relationship studies reveal the critical role of the α,β-unsaturated carbonyl group in its bioactivity. Despite promising preclinical evidence, clinical validation remains necessary to establish zerumbone's therapeutic potential for colorectal cancer management.